Perbedaan ketebalan odontoblast-like cells setelah aplikasi CAPE dan Kalsium Hidroksida - Putri Galuh Prawitasari; Karlina Samadi; Ari Subiyanto (Conservative Dentistry Journal, 2018)
Background : CAPE is the main component of propolis, it has several biology and fpharmocological advantages as antioxidant, antiinflammation, anticancer and as an immunomodulator. There were the research before of CAPE is capable to stimulate the production of the TGF-β 1 and collagen sintesis by the pulp tissue with many superiority compare to Ca(OH)2, recently Ca(OH)2 is  the gold standard for pulp capping treatment procedure. Objective : To determine and compare the effectiveness of CAPE and Ca(OH)2 to the thickness of odontoblast-like cells in rat pulp tissue. Methods : Maxillary first molar tooth of wistar mice was class 1 preparated until the pulp opened, then Ca(OH)2 was aplicated for 14 and 28 days, CAPE for 14 and 28 days. After application of Ca(OH)2 and propolis extract, the tooth was filled with RMGIC. Teeth were extracted on defined day and processed for histological evaluation. Result : There is a significant difference in the thickness of odontoblast-like cells after application of CAPE for 14 days with Ca(OH)2 for 14 days and CAPE for 28 days with Ca(OH)2 for 28 days. Conclusion : odontoblast-like cells after aplication of CAPE extract material is thicker than Ca(OH)2.